5‐Aminolevulinic acid/sodium ferrous citrate enhanced the antitumor effects of programmed cell death‐ligand 1 blockade by regulation of exhausted T cell metabolism in a melanoma model. Issue 7 (22nd May 2021) - Hu, Xin; Que, Weitao; Hirano, Hiroshi; Wang, Zhidan; Nozawa, Naoko; Ishii, Takuya; Ishizuka, Masahiro; Ito, Hidenori; Takahashi, Kiwamu; Nakajima, Motowo; Tanaka, Tohru; Zhu, Ping; et al.
Abstract: Mitochondria are key cytoplasmic organelles. Their activation is critical for the generation of T cell proliferation and cytotoxicity. Exhausted tumor‐infiltrating T cells show a decreased mitochondrial function and mass. 5‐Aminolevulinic acid (5‐ALA), a natural amino acid that is only produced in the mitochondria, has been shown to influence metabolic functions. We hypothesized that 5‐ALA with sodium ferrous citrate (SFC) might provide metabolic support for tumor‐infiltrating T cells. In a mouse melanoma model, we found that 5‐ALA/SFC with a programmed cell death‐ligand 1 (PD‐L1) blocking Ab synergized tumor regression. After treatment with 5‐ALA/SFC and anti‐PD‐L1 Ab, tumor infiltrating lymphocytes (TILs) were not only competent for the production of cytolytic particles and cytokines (granzyme B, interleukin‐2, and γ‐interferon) but also showed enhanced Ki‐67 activity (a proliferation marker). The number of activated T cells (PD‐1 + Tim‐3 − ) was also significantly increased. Furthermore, we found that 5‐ALA/SFC activated the mitochondrial functions, including the oxygen consumption rate, ATP level, and complex V expression. The mRNA levels of Nrf‐2, HO‐1, Sirt‐1, and PGC‐1α and the protein levels of Sirt‐1 were upregulated by treatment with 5‐ALA/SFC. Taken together, our findings revealed that 5‐ALA/SFC could be a key metabolic regulator in exhausted T cell metabolism and suggested that 5‐ALA/SFC might synergize with anti‐PD‐1/PD‐L1 therapy to boost the intratumoral efficacy of tumor‐specific T cells. Our study not only revealed a new aspect of immune metabolism, but also paved the way to develop a strategy for combined anti‐PD‐1/PD‐L1 cancer immunotherapy. Abstract : Exhausted T cells have decreased effector and proliferation function. We found that the mRNA levels of the Nrf‐2, HO‐1, Sirt‐1, and PGC‐1α and the protein levels of Sirt‐1 were upregulated by treatment with 5‐aminolevulinic acid (5‐ALA)/sodium ferrous ion (SFC). The enforced expression of PGC‐1α in activated T cells rescued their effector function and enhanced the efficacy of the mitochondrial function. Our findings revealed that 5‐ALA/SFC could be a key metabolic regulator in exhausted T cell metabolism and suggested that 5‐ALA/SFC might synergize with anti‐programmed cell death‐1/programmed cell death‐ligand 1 therapy to boost the intratumoral efficacy of tumor‐specific T cells. ​